Biomechanical analysis of sacroiliac joint motion following oblique-pulling manipulation with or without pubic symphysis injury - Li, Jing; Li, Yikai; Ping, Ruiyue; Zhang, Qing; Chen, Hai-Yun; Lin, Dingkun; Qi, Ji (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Oblique-pulling manipulation has been widely applied in treating sacroiliac joint (SIJ) dysfunction. However, little is known about the biomechanical mechanism of the manipulation. This study aimed to analyze the SIJ motion under oblique-pulling manipulation, in comparison with compression and traction loads. Methods/Study Design: Six specimens of embalmed human pelvis cadavers were dissected to expose the SIJ and surrounding ligaments. Through a servo-hydraulic testing system, biomechanical tests were performed on the stable pelvis and the unstable pelvis with pubic symphysis injury (PSI). A three-dimensional (3D) photogrammetry system was employed to determine the separation and nutation in three tests: axial compression (test A), axial traction (test B), and oblique-pulling manipulation (test C). Results: After applying the testing loads, the range of nutation was no more than 0.3° (without PSI) and 0.5°(with PSI), separately. Except for test B, a greater nutation was found with PSI (P<0.05). Under both conditions, nutation following test A was significantly greater than that of other tests (P<0.05). SIJ narrowed in test A and separated in tests B and C, where the range of motion did not exceed 0.1mm (without PSI) or 0.3mm (with PSI) separately. Under both conditions, the separation of SIJ in test C was not as apparent as the narrowness of SIJ in test A (P<0.05). Compared to SIJ, a more significant increasing displacement was found at the site of the iliolumbar ligament (P<0.05). Nevertheless, when the force was withdrawn in all tests, the range of nutation and separation of SIJ nearly decreased to the origin. Conclusion: Pubic Symphysis is essential to restrict SIJ motion, and the oblique-pulling manipulation could cause a weak nutation and separation of SIJ. However, the resulting SIJ motion might be neutralized by regular standing and weight-bearing load. Also, the effect on SIJ seems to disappear at the end of manipulation. Therefore, the stretching and loosening of surrounding ligaments need to be paid more attention to.